Klasifikasi Tingkat Maturitas Katarak Berbasis Citra Digital Berdasarkan Jangkauan (Range) Nilai Histogram - Gede Arya Wiguna; Ramacos Fardela; Jannes Bastian Selly (Fakultas Pertanian, Universitas Timor, 2019)
Cataract is an eye disorder that is at risk of causing blindness. The risk of blindness can be prevented by detecting cataracts as well as the right action in the form of surgery. Examination of cataracts in the eye poly usually uses equipment in the form of a slit lamp. This equipment is only available in hospitals that have eye poly. The lack of hospitals that have slit lamps will cause the number of cataract sufferers to increase. To be able to help overcome this we need a cataract detection system that is easy to implement. In this research, a classification system based on digital image based on the range of histogram values ​​was made. The equipment used to obtain digital images is the Nikon D90 12.3 Megapixel camera with Nikon 50 mm F1.8 AFD lens. The results obtained indicate that the range values ​​for normal eyes are 29–46, immature eyes 54 - 67 and mature eyes 91 - 121. It appears that mature eyes have the highest range. It is hoped that this method can help detect and classify cataracts based on digital image processing.